Lincoln building ruins at the corner of Essex and Lincoln Streets, 1893 - Clark, William T. (Tufts Archival Research Center, 2005)
Elevated view looking south of the ruins of the Lincoln building destroyed by fire. On the left is Essex Street and on the right Lincoln Street. Fire hoses are seen spraying water on the debris. Fireman and onlookers are seen in the image. Smoke obscures the background view. Written in pencil on mount, this wall taken down and Essex Street widened 7 5/8 x 8 1/4 overall 9 5/8 x 9 1/2 Photographs